Optimization of Oral Disentegrating Film (ODF) Matrix from Alginate and Pectin/Gum Acacia/Carrageenan Polymer Using PEG/Glycerol as Plasticizer - Viviane Annisa; Fajar Aji Lumakso; Ghiffari Ahnaf Danarwindu; Khasbi Andi Irawan (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Oral dispersible film (ODF) is an innovative oral drug dosage form that is easy to consume, especially by pediatric, geriatric, and low-compliance patients. This preparation quickly disintegrates in the mouth without the need for water, providing a rapid onset of action, high bioavailability, and comfort of use. Hydrophilic polymers such as alginate are often used because they form strong films and dissolve readily in saliva. One important component in ODF formulations is a plasticizer, which increases flexibility and reduces film fragility. Two common plasticizers used are polyethylene glycol (PEG) and glycerol, each with different characteristics. This research method uses solvent casting. The polymers used are combinations of alginate:pectin, alginate:gum acacia, and alginate: carrageenan, with ratios of 3:0, 3:1, 3:2, 2:2, 2:1, and 0:3. Each polymer formulation was given additional PEG400 or glycerol at three concentration levels: 1%, 2.5%, and 5%. All formulas were tested for organoleptic, physical characteristics, disintegration time, strength, elongation, Scanning Electron Microscopy (SEM), and FTIR. The selection of glycerol and PEG400 plasticizers can affect disintegration time, tensile strength, elongation percentage, and SEM. Polymers also affect film characteristics, including the type of polymer and the concentration of the combined polymers.